A composite quaternary positive electrode material and its preparation method and application

By forming a graphene cladding layer on the quad-alloy positive electrode material, the problem of low stability of high-nickel ternary layered oxide material is solved, and the cycle stability and safety of lithium-ion batteries are significantly improved.

CN115117326BActive Publication Date: 2025-04-04JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210949232.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-09
Publication Date
2025-04-04
Estimated Expiration
2042-08-09

AI Technical Summary

Technical Problem

High-nickel ternary layered oxide materials have low stability in lithium-ion batteries, which affects their circulation performance and safety, thereby limiting their application in the field of power batteries.

Method used

By adding the quaternary positive electrode material powder to the polyvinyl alcohol water sol, graphene oxide is coated on the quaternary positive electrode with polyvinyl alcohol, and thermal reduction treatment is performed under a protective atmosphere to reduce the damage of graphene and form a graphene clad layer.

Benefits of technology

The coating layer with good graphene bonding status and low damage is achieved, which improves the cycle stability and safety of the quaternary positive electrode material, and significantly improves the discharge specific capacity and cycle capacity retention rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a composite quaternary positive electrode material and a preparation method and application thereof, wherein the preparation method comprises the following steps: (1) mixing the quaternary positive electrode material with polyvinyl alcohol sol to obtain a quaternary positive electrode slurry; (2) mixing the quaternary positive electrode slurry with a graphene oxide dispersion, and subjecting the mixture to thermal reduction treatment to obtain the composite quaternary positive electrode material. The present invention uses polyvinyl alcohol to coat graphene oxide on a quaternary positive electrode, and then thermally reduces the quaternary positive electrode coated with graphene under a protective atmosphere, thereby obtaining a graphene coating layer with good graphene bonding and low damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a composite quaternary positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been widely used in electric vehicles, 3C electronics, energy storage and other fields. At present, new energy vehicles occupy an increasing share in the market. However, if new energy vehicles want to develop further and completely replace traditional fuel vehicles, they need to solve the problem of "range anxiety", which requires the core component of new energy vehicles - power lithium batteries to have higher energy density. In order to meet this requirement, we need to select a positive electrode material with high energy density and stable operation.

[0003] At present, in the field of power batteries, the main cathode materials used are lithium iron phosphate and ternary layered oxide materials. Among them, lithium iron phosphate has the advantages of low cost, good cycle performance and good safety, but its capacity is low, and with the improvement of the process, the specific capacity has been getting closer and closer to its theoretical limit, and there is little room for improvement in the future, and the poor low-temperature performance also limits its application range; ternary layered oxide materials have good capacity density, good cycle performance and high compaction density, and with the increase of Ni content, its actual specific capacity also increases. In solving the problem of "mileage anxiety", ternary layered oxide materials have more advantages. Therefore, in future development, ternary layered oxide materials will gradually occupy the mainstream position in the field of power batteries.

[0004] Although high-nickel ternary layered oxide materials have high specific capacity, the high Ni content also reduces their stability, which makes the cycle performance and safety of high-nickel materials worse, which greatly affects their application in the field of power batteries. Therefore, how to improve the stability of high-nickel ternary layered oxide materials has become a research hotspot for some scientists. It is currently believed that doping and coating are effective means to improve stability. The introduction of doping elements can make quaternary positive electrode materials and thus construct a more stable positive electrode material structure; while the coating of graphene can improve the conductivity of the material while suppressing side reactions, and give full play to the performance of the active material.

[0005] CN105633381A discloses a method for preparing a graphene-based composite nickel-cobalt-aluminum-titanium quaternary positive electrode material, which prepares the nickel-cobalt-aluminum-titanium quaternary material by a chemical coprecipitation method; a solid carbon source and the nickel-cobalt-aluminum-titanium quaternary material are mixed and ball-milled at a mass ratio of 3:0.1-1 to obtain a mixture; the mixture is evaporated onto the surface of a silicon substrate by an organic evaporation coating apparatus to obtain a sample A; a metal catalyst is uniformly evaporated on the surface of sample A to obtain a sample B; sample B is placed in a quartz tube, and then placed in a tubular furnace for vacuum sintering to obtain a perfectly coated graphene-based nickel-cobalt-aluminum-titanium quaternary positive electrode material.

[0006] CN113443659A discloses a quaternary positive electrode material co-modified by wet doping and carbon coating and a preparation method thereof, which combines the two modification methods of wet doping and surface coating through the quaternary positive electrode material co-modified by wet doping and carbon coating, and wet doping and modification are performed through co-precipitation reaction, and the doping elements are evenly distributed.

[0007] In the quaternary positive electrode material described in the above scheme, the bonding state between graphene and the positive electrode material is poor, and part of the graphene will re-aggregate during the drying process, affecting the material performance. Summary of the invention

[0008] The purpose of the present invention is to provide a composite quaternary positive electrode material and a preparation method and application thereof. The present invention adds quaternary positive electrode material powder to polyvinyl alcohol aqueous sol, and uses polyvinyl alcohol to coat graphene oxide on the quaternary positive electrode. By heat treatment under a protective atmosphere, the damage to graphene can be minimized.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a composite quaternary positive electrode material, the preparation method comprising the following steps:

[0011] (1) mixing a quaternary positive electrode material with a polyvinyl alcohol sol to obtain a quaternary positive electrode slurry;

[0012] (2) The quaternary positive electrode slurry is mixed with the graphene oxide dispersion, and the composite quaternary positive electrode material is obtained by thermal reduction treatment.

[0013] The present invention uses polyvinyl alcohol to coat graphene oxide on a quaternary positive electrode, and then obtains a graphene-coated quaternary positive electrode by thermal reduction in a protective atmosphere, thereby obtaining a graphene coating layer with good graphene bonding state and low damage.

[0014] Preferably, the chemical formula of the quaternary positive electrode material in step (1) is LiNi x Co y Mn z M(1-x-y-z) O 2 , wherein x is 0.80 to 0.99, y is 0.01 to 0.20, z is 0.01 to 0.20, and M is any one of tungsten, aluminum, magnesium, titanium, zirconium, boron, tantalum or molybdenum.

[0015] Preferably, the solvent of the polyvinyl alcohol sol in step (1) includes water.

[0016] Preferably, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol sol is 1-5%, for example, 1%, 2%, 3%, 4% or 5%.

[0017] Preferably, stirring is performed during the mixing process in step (1).

[0018] Preferably, the stirring time is 1 to 4 hours, for example, 1 hour, 2 hours, 3 hours or 4 hours.

[0019] Preferably, the mass ratio of the quaternary positive electrode material to the polyvinyl alcohol sol in step (1) is 1:(2-10), for example: 1:2, 1:4, 1:6, 1:8 or 1:10, etc.

[0020] Preferably, the mass fraction of graphene oxide in the graphene oxide dispersion in step (2) is 1 to 3%, for example: 1%, 1.5%, 2%, 2.5% or 3%, etc.

[0021] Preferably, the volume ratio of the graphene oxide dispersion to the quaternary positive electrode slurry is (0.2-1):1, for example: 0.2:1, 0.4:1, 0.6:1, 0.8:1 or 1:1, etc.

[0022] Preferably, stirring is performed during the mixing process.

[0023] Preferably, the stirring time is 1 to 4 hours, for example, 1 hour, 2 hours, 3 hours or 4 hours.

[0024] Preferably, the mixing is followed by drying.

[0025] Preferably, the drying temperature is 50-80°C, for example, 50°C, 60°C, 70°C or 80°C.

[0026] Preferably, the atmosphere of the thermal reduction treatment in step (2) comprises nitrogen and / or argon.

[0027] Preferably, the temperature of the thermal reduction treatment is 300-500°C, for example, 300°C, 350°C, 400°C, 450°C or 500°C.

[0028] Preferably, the thermal reduction treatment time is 1 to 3 hours, for example: 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.

[0029] In a second aspect, the present invention provides a composite quaternary positive electrode material, and the composite quaternary positive electrode material is prepared by the method described in the first aspect.

[0030] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the composite quaternary positive electrode material as described in the second aspect.

[0031] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The present invention uses polyvinyl alcohol to coat graphene oxide on a quaternary positive electrode, and then obtains a graphene-coated quaternary positive electrode by thermal reduction under a protective atmosphere, thereby obtaining a graphene coating layer with good graphene bonding and low damage.

[0034] (2) The battery made of the composite quaternary positive electrode material of the present invention has a discharge capacity of more than 214.11 mAh / g at 0.1C, and a capacity retention rate of more than 96.36% after 50 cycles at 1C, indicating that the graphene-coated quaternary positive electrode obtained by the present invention has good discharge capacity and good cycle stability. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0036] The quaternary positive electrode materials used in the embodiments of the present invention and the comparative examples are all prepared by the following method:

[0037] (1) nickel sulfate, cobalt sulfate, manganese sulfate, and aluminum sulfate were weighed according to the stoichiometric ratio of Ni:Co:Mn:Al=0.9:0.04:0.05:0.01 to prepare a 2 mol / L quaternary solution;

[0038] (2) Add the bottom liquid into the reactor and pass N 2 , the temperature was raised to 60°C, the quaternary solution, sodium hydroxide solution and ammonia solution in step 1 were added to the reactor in parallel and stirred continuously, the pH of the reaction system was maintained at 10.8 to 11.2, and the reaction was carried out for 80 hours to obtain Ni 0.9 Co 0.04 Mn 0.05 Al 0.01 (OH) 2A quasi-spherical quaternary precursor; wherein the concentration of the sodium hydroxide solution and the ammonia solution is 2 mol / L; the stirring speed is 350 to 400 r / min;

[0039] (3) After washing, drying, sieving and removing iron from the above precursor powder, the mixture was mixed with lithium carbonate in a ratio of 1.2:1 and kept at 500°C for 3 hours, then heated to 900°C for 12 hours to obtain LiNi 0.9 Co 0.04 Mn 0.05 Al 0.01 O 2 Quaternary cathode materials.

[0040] Example 1

[0041] This embodiment provides a composite quaternary positive electrode material, and the preparation method of the composite quaternary positive electrode material is as follows:

[0042] (1) adding quaternary cathode material powder to 3% polyvinyl alcohol aqueous sol by mass, and stirring for 3 hours to form quaternary cathode slurry; wherein the mass ratio of quaternary cathode material powder to polyvinyl alcohol aqueous sol is 1:5;

[0043] (2) A certain amount of graphene oxide dispersion was pumped into the above-mentioned quaternary cathode slurry, stirred for 3 h, washed the powder and dried it at 60 °C, and then heated it under N 2 The composite quaternary positive electrode material is obtained by thermal reduction at 300° C. for 2 hours under an atmosphere; wherein the mass fraction of graphene oxide in the graphene oxide dispersion is 2%; and the volume ratio of the graphene oxide dispersion to the quaternary positive electrode slurry is 0.2:1.

[0044] Example 2

[0045] This embodiment provides a composite quaternary positive electrode material, and the preparation method of the composite quaternary positive electrode material is as follows:

[0046] (1) adding quaternary cathode material powder to 3.5% polyvinyl alcohol aqueous sol by mass, and stirring for 2.8 hours to form quaternary cathode slurry; wherein the mass ratio of quaternary cathode material powder to polyvinyl alcohol aqueous sol is 1:6;

[0047] (2) A certain amount of graphene oxide dispersion was pumped into the above-mentioned quaternary cathode slurry, stirred for 3 h, washed the powder and dried it at 65 °C, and then heated it under N 2 The composite quaternary positive electrode material is obtained by thermal reduction at 350° C. for 2 hours under an atmosphere; wherein the mass fraction of graphene oxide in the graphene oxide dispersion is 2.2%; and the volume ratio of the graphene oxide dispersion to the quaternary positive electrode slurry is 0.3:1.

[0048] Example 3

[0049] The only difference between this embodiment and embodiment 1 is that the mass fraction of polyvinyl alcohol in the polyvinyl alcohol sol is 0.5%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0050] Example 4

[0051] The only difference between this embodiment and embodiment 1 is that the mass fraction of polyvinyl alcohol in the polyvinyl alcohol sol is 6%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0052] Example 5

[0053] The only difference between this embodiment and embodiment 1 is that the mass ratio of the quaternary positive electrode material to the polyvinyl alcohol sol is 1:1, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0054] Example 6

[0055] The only difference between this embodiment and embodiment 1 is that the mass ratio of the quaternary positive electrode material to the polyvinyl alcohol sol is 1:12, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0056] Example 7

[0057] The only difference between this embodiment and embodiment 1 is that the mass fraction of graphene oxide in the graphene oxide dispersion is 0.5%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0058] Example 8

[0059] The only difference between this embodiment and embodiment 1 is that the mass fraction of graphene oxide in the graphene oxide dispersion is 4%, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0060] Comparative Example 1

[0061] The only difference between this comparative example and Example 1 is that the quaternary positive electrode material is added after the graphene and the polyvinyl alcohol sol are mixed, and the other conditions and parameters are exactly the same as those in Example 1.

[0062] Performance Test:

[0063] The quaternary positive electrode material coated in the embodiment was used as the positive electrode material, and the positive electrode material, carbon black conductive agent, binder PVDF and NMP in a mass ratio of 95:2.5:2.5:5 were mixed evenly to prepare the positive electrode slurry of the battery. The slurry was coated on an aluminum foil with a thickness of 20 to 40 μm, and the positive electrode sheet was made after vacuum drying and rolling. The lithium metal sheet was used as the negative electrode, and the electrolyte ratio was 1.15M LiPF 6EC:DMC (1:1 vol%), and assembled button batteries, and performed charge and discharge comparison tests on the button batteries. The test results are shown in Table 1:

[0064] Table 1

[0065]

[0066]

[0067] As can be seen from Table 1, from Examples 1-2, the discharge specific capacity of the battery made of the composite quaternary positive electrode material of the present invention can reach more than 214.11 mAh / g at 0.1C, and the capacity retention rate can reach more than 96.36% after 50 cycles at 1C.

[0068] By comparing Example 1 with Examples 3-4, it can be seen that in the preparation process of the composite quaternary positive electrode material described in the present invention, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol sol will affect the performance of the obtained positive electrode material. When the mass fraction of polyvinyl alcohol in the polyvinyl alcohol sol is controlled at 1-5%, the performance of the obtained positive electrode material is better. If the mass fraction of polyvinyl alcohol in the polyvinyl alcohol sol is too large, the viscosity of the sol will be too large, which is not conducive to the dispersion of the subsequently added graphene oxide. If the mass fraction of polyvinyl alcohol in the polyvinyl alcohol sol is too small, the coating effect of graphene oxide will be poor.

[0069] By comparing Example 1 with Examples 5-6, it can be seen that in the preparation process of the composite quaternary positive electrode material of the present invention, the mass ratio of the quaternary positive electrode material to the polyvinyl alcohol sol will affect the performance of the obtained positive electrode material. When the mass ratio of the quaternary positive electrode material to the polyvinyl alcohol sol is controlled at 1:(2-10), the performance of the obtained positive electrode material is better. If the mass ratio of the quaternary positive electrode material to the polyvinyl alcohol sol is too large, the final coated graphene content will be reduced, and the performance improvement will be limited. If the mass ratio of the quaternary positive electrode material to the polyvinyl alcohol sol is too small, the graphene will re-aggregate during the subsequent heat treatment process.

[0070] By comparing Example 1 with Examples 7-8, it can be seen that in the preparation process of the composite quaternary positive electrode material of the present invention, the mass fraction of graphene oxide in the graphene oxide dispersion will affect the performance of the obtained positive electrode material. The mass fraction of graphene oxide in the graphene oxide dispersion is controlled at 1-3%, and the performance of the obtained positive electrode material is better. If the mass fraction of graphene oxide in the graphene oxide dispersion is too large, the dispersibility of graphene oxide in the dispersion will deteriorate, further affecting the performance of the subsequent coating material. If the mass fraction of graphene oxide in the graphene oxide dispersion is too small, the coating amount will be reduced.

[0071] By comparing Example 1 with Comparative Example 1, it can be seen that the feeding method of the present invention can make polyvinyl alcohol first form a film on the positive electrode particles, which is more conducive to the subsequent addition of graphene to form a complete coating layer.

[0072] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite quaternary positive electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing a quaternary positive electrode material with a polyvinyl alcohol sol to obtain a quaternary positive electrode slurry; The mass ratio of the quaternary positive electrode material to the polyvinyl alcohol sol is 1:(2-10); (2) The quaternary positive electrode slurry is mixed with the graphene oxide dispersion, and the composite quaternary positive electrode material is obtained by thermal reduction treatment.

2. The preparation method according to claim 1, characterized in that The chemical formula of the quaternary positive electrode material in step (1) is LiNi x Co y Mn z M (1-x-y-z) O2, wherein x is 0.80 to 0.99, y is 0.01 to 0.20, z is 0.01 to 0.20, and M is any one of tungsten, aluminum, magnesium, titanium, zirconium, boron, tantalum or molybdenum.

3. The preparation method according to claim 1, characterized in that: The solvent of the polyvinyl alcohol sol in step (1) includes water.

4. The preparation method according to claim 1, characterized in that: The mass fraction of polyvinyl alcohol in the polyvinyl alcohol sol in step (1) is 1-5%.

5. The preparation method according to claim 1, characterized in that: Stirring is performed during the mixing process in step (1).

6. The preparation method according to claim 5, characterized in that: The stirring time is 1 to 4 hours.

7. The preparation method according to claim 1, characterized in that: The mass fraction of graphene oxide in the graphene oxide dispersion in step (2) is 1 to 3%.

8. The preparation method according to claim 1, characterized in that: The volume ratio of the graphene oxide dispersion to the quaternary positive electrode slurry in step (2) is (0.2-1):

1.

9. The preparation method according to claim 1, characterized in that: Stirring is performed during the mixing process in step (2).

10. The preparation method according to claim 9, characterized in that: The stirring time is 1 to 4 hours.

11. The preparation method according to claim 1, characterized in that: The mixing in step (2) is followed by drying.

12. The preparation method according to claim 11, characterized in that: The drying temperature is 50-80°C.

13. The preparation method according to claim 1, characterized in that: The atmosphere for the thermal reduction treatment in step (2) includes nitrogen and / or argon.

14. The preparation method according to claim 1, characterized in that: The temperature of the thermal reduction treatment in step (2) is 300-500°C.

15. The preparation method according to claim 1, characterized in that: The time of the thermal reduction treatment in step (2) is 1 to 3 hours.

16. A composite quaternary positive electrode material, characterized in that: The composite quaternary positive electrode material is prepared by the method as described in any one of claims 1-15.

17. A positive electrode plate, characterized in that: The positive electrode sheet comprises the composite quaternary positive electrode material as claimed in claim 16.

18. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 17.

Citation Information

Patent Citations

  • Wet doping and carbon coating co-modified quaternary positive electrode material and preparation method thereof

    CN113443659A

  • Preparation method for graphene-based composite nickel cobalt aluminum titanium quaternary material

    CN105633381A

  • Composite cathode material and preparation method thereof and lithium ion battery

    CN105762345A